Analisis Multivariat pada Struktur Komunitas Mangrove di Kecamatan Rupat Utara Kabupaten Bengkalis Provinsi Riau - Syahrial Syahrial; Muhammad Hatta; Chandrika Eka Larasati; Arina Ruzanna; Al Muzafri; La Ode Abdul Fajar Hasidu; Windi Syahrian; Zan Zibar (Jurnal Kelautan Tropis, 2023)
Increasing human activity in all aspects of life has contributed to the decline of mangrove forests, a multivariate analysis study on the structure of the mangrove community was conducted in July 2018 in North Rupat District, Bengkalis Regency, Riau Province with the objective of estimating or assessing the condition of the mangrove community structure. Data on the condition of mangrove vegetation was collected in six observations using line transects and plots measuring 10 x 10 m. Mangrove diversity was analyzed using the Shannon-Weaver and Simpson indexes, and variations in mangrove community the structure was analyzed using clusters, non-metric MDS, ANOSIM, and SIMPER. The study discovered 12 mangrove species in North Rupat District, Bengkalis Regency, Riau Province, which was classified into 6 families based on diversity analysis (H') Shannon Weaver indexes ranging from 01.34 to 01.72 and Simpson indexes ranging from 02.43 to 02.81. Furthermore, the results of the mangrove diversity analysis using multivariate clusters and non-metric MDS were divided into four groups, and while the cluster analysis based on the value of the mangrove density had a similarity of 60%, the variation in the significance of mangrove density was significantly different (R = 0.689, p = 0.000), and the mangrove species that compose varies between stations. Moreover, the trunk diameter of mangrove vegetation in North Rupat District, Bengkalis Regency, Riau Province is dominated by mangrove stands with a trunk diameter of 01.00 - 20.00 cm, with the mangrove vegetation that grows and develops at Stations 2 and 6 being relatively younger than the other stations. Stations 3 and 4 are considered more mature in terms of growth and development.  Peningkatan aktivitas manusia di segala setor kehidupan telah mendorong penurunan hutan mangrove, sehingga kajian analisis multivariat pada struktur komunitas mangrove di Kecamatan Rupat Utara Kabupaten Bengkalis Provinsi Riau telah dilakukan pada bulan Juli 2018 dengan tujuan untuk mengestimasi atau menilai kondisi struktur komunitas mangrovenya. Data kondisi vegetasi mangrove dikumpulkan pada enam stasiun pengamatan dengan membuat transek garis dan plot yang berukuran 10 x 10 m, kemudian keanekaragaman mangrovenya dianalisis menggunakan indeks Shannon-Weaver dan Simpson, sedangkan variasi struktur komunitas mangrovenya dianalisis berdasarkan cluster, non-metric MDS, ANOSIM dan SIMPER. Hasil kajian menemukan 12 spesies mangrove di Kecamatan Rupat Utara Kabupaten Bengkalis Provinsi Riau yang tergolong ke dalam 6 famili dengan analisis keanekaragaman (H’) indeks Shannon Weaver berkisar antara 01.34 – 01.72 dan indeks Simpson berkisar antara 02.43–02.81, kemudian hasil analisis keanekaragaman mangrovenya dengan multivariat cluster dan non-metric MDS terbagi atas empat kelompok, sedangkan analisis cluster berdasarkan nilai kerapatan mangrovenya memiliki kemiripan ± 60%, variasi signifikansi kerapatan mangrovenya berbeda nyata (R = 0.689, p = 0.000) serta spesies mangrove penyusun antar stasiun pengamatannya bervariasi. Selain itu, diameter batang vegetasi mangrove di Kecamatan Rupat Utara Kabupaten Bengkalis Provinsi Riau didominasi oleh tegakan mangrove berdiameter batang 01.00 – 20.00 cm, dimana vegetasi mangrove yang tumbuh dan berkembang di Stasiun 2 maupun 6 tergolong lebih muda dibandingkan stasiun yang lainnya, sedangkan vegetasi mangrove yang tumbuh dan berkembang di Stasiun 3 maupun 4 tergolong lebih matang.